Decriminalization of medical hashish use for the treatment of epilepsy patients in indonesia - Hernanda Priambudi; Aan Asphianto; Ahmad Fauzi (Universitas Dharmawangsa Medan, 2025)
Legal policies in several countries have legalized the use of cannabis for medical purposes, while in Indonesia the law still prohibits the use of cannabis for medical purposes because it is still placed in the type of narcotics Schedule I. This condition shows that the law is not responsive, not adaptive to the needs of society, namely patients with certain diseases who need drugs containing medical cannabis to cure their illnesses. The purpose of the study is: what is the urgency of regulating medical cannabis for the treatment of epilepsy in Indonesia. The research method used is normative legal research with a statute approach and a conceptual approach.